STRESS AND LONGEVITY IN AFRICAN AMERICAN FAMILIES. (11th November 2018) - Whitfield, K E; Thorpe, R J; Brown, T; Barker, C; Maher, B; Hauser, M
Abstract: At 65, remaining life expectancy of African Americans is about two years less than Caucasians. However, some estimates suggest that after age 85 African Americans may have a longevity advantage. The African Americans who survive into late life have done so despite social and health disadvantages. However, the literature on longevity often focuses on only genetic predisposition. There is a critical need to understand how the intersections between social, biological and behavioral factors impact longevity in African Americans. The goal of our work is to examine patterns of stress, coping, health and genes which contribute to longevity among 300 African American families. We are pursuing the following questions: 1) Do familial effects create similarities between siblings' stress and coping? 2) Does stress account for differences in patterns of longevity in families? 3) Do genes influence patterns of stress, coping, health status, and longevity?